The Open-Ended Problem Solving in Mathematics Class of Grade 6 Students - Pongpullponsak, Assoc.Adisak; Kulchantawit, Jiraporn (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2009)
The objective of this research was to study the result ofopen-ended problem solving methods in mathematics classinstruction of Grade-6 students. Three open-ended problemsolving activities had been implemented, including thoseactivities related to geometry, arithmetic and problem solvingskills, with 61 grade-6 students of Wat Chang Lek and RasPadung Pol schools. The data collecting tools includedevaluation and scoring criteria form, learning efficiencyevaluation form and mathematic learning attitude evaluationform. The statistics tools included average value, standarderrors, data presentation (table and descriptive). In learningefficiency comparison, the statistics term "t" was employed tocompare learning efficiency of two groups of students. Theresult indicated that there was no difference in learningefficiency between two methods while the attitude inmathematics learning, with open-ended problem solvingmethod, of the students in the experimental group was in"strongly agree" level. The thinking behavior, in problem solving by each aspect, of students in the same experimental group (in both small sub groups and individual) was in "good" level.